2022
DOI: 10.1161/jaha.122.025676
|View full text |Cite
|
Sign up to set email alerts
|

RNF213 R4810K Variant in Suspected Unilateral Moyamoya Disease Predicts Contralateral Progression

Abstract: Background Early‐stage unilateral moyamoya disease (MMD) is difficult to discriminate from isolated intracranial atherosclerotic stenosis, and identification of contralateral progression may aid in the diagnosis of MMD. The RNF213 (ring finger protein 213) R4810K variant is a strong genetic susceptibility factor for MMD; however, the role of contralateral progression in unilateral MMD is unknown. Methods and Results Patients who had under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
(36 reference statements)
0
0
0
Order By: Relevance
“…Recent research has identified several susceptibility genes, including individuals diagnosed with familial moyamoya disease, that have the 95% p. R4810K variant in the RNF213 gene [3]. Studies have found that Moyamoya disease is more common in individuals of Asian descent, with a higher prevalence observed in Japan where the condition was first discovered [4]. Interestingly, MMD is linked to have an association with mutations in human RNF213 and ACTA2 genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has identified several susceptibility genes, including individuals diagnosed with familial moyamoya disease, that have the 95% p. R4810K variant in the RNF213 gene [3]. Studies have found that Moyamoya disease is more common in individuals of Asian descent, with a higher prevalence observed in Japan where the condition was first discovered [4]. Interestingly, MMD is linked to have an association with mutations in human RNF213 and ACTA2 genes.…”
Section: Introductionmentioning
confidence: 99%
“…MMD has a bimodal distribution, with peaks between the ages of 5 to 10 years in children and then between ages 30 -50 years in adults; the population of patients from the second peak is smaller than the first. MMD has a family history, which is positive in 10% -15% of patients with initial onset followed by slow progression [4] [5]. According to a prospective study involving 23 patients diagnosed with ischemic MMD using DSA, it was discovered that TGFβ1 is crucial in facilitating the development of collateral blood vessels by increasing the expression of VEGF in ischemic MMD.…”
Section: Introductionmentioning
confidence: 99%